Investigating the effects of NaOH molarity and the geometry of PVA fibers on the post-cracking and the fracture behavior of engineered geopolymer composite - Zahid, M. (Elsevier Ltd, 2020)
This paper presents an experimental study on improving the post-cracking and the fracture behavior of engineered geopolymer composite containing polyvinyl alcohol (PVA) fibers. Two classes of fibers designated as coarse and fine were investigated. The single fiber volume governed the total number of fibers dispersed in the unit volume of the matrix (Nv), which caused significant effects on the post-cracking and the fracture behavior of the composite. The molarity of the NaOH solution is an important parameter that controlled the geopolymerization process and affected the strength and other properties of the composite. Three different molarity of NaOH solution, 8 M, 12 M, and 16 M, were investigated. The results showed that the specimens made of 8 M matrix containing fine fibers (0.04 mm diameter and 8 mm and 12 mm in length) performed well in the post-cracking stage and satisfied the criteria for pseudo strain hardening (PSH). The direct tensile strength results showed that 8 mm and 12 mm long fine fibers in the 8 M matrix achieved the strength ratio of ultimate to the first crack strength as 1.7 and 1.66, respectively. The strength ratio criterion for PSH suggested a value greater than 1.3. Similarly, from the notched-beam bending test, the energy performance index of 8 mm, and 12 mm long fine fibers in the 8 M matrix were estimated as 7.77 and 6.52, respectively. In contrast, a value of greater than 3 is recommended for PSH behavior. Fine fibers added in the 12 M and 16 M matrix also satisfied the criteria for PSH behavior. Whereas, the coarse fibers (0.2 mm diameter and 18 mm and 24 mm in length) performed well in resisting direct compression and showed higher fracture energy and the modulus of elasticity. The best combination was observed as a 12 M matrix containing fine fibers of 0.04 mm diameter and 8 mm in length. Â© 2020 Elsevier Ltd